2023
DOI: 10.7759/cureus.33202
|View full text |Cite
|
Sign up to set email alerts
|

Improving Risk Stratification of Patients With Chest Pain in the Emergency Department

Abstract: Objective: The HEARTS3 score is used to predict acute coronary syndrome by evaluating the findings of chest pain patients at the end of the second hour. Additionally, the American College of Cardiology (ACC)/American Heart Association (AHA) 2014 non-ST elevation acute coronary syndrome (NSTE-ACS) management guideline suggests assessing cardiac troponin levels at the third and sixth hours as a class 1A recommendation. This study aimed to explore the value of the HEARTS3 score for the evaluation of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In order to balance the risk between a hasty discharge versus the potential harms caused by a cardiac assessment in patients admitted to the ED with suspected acute cardiovascular disease, the recent expert documents and guidelines recommend the measurement of specific cardiac biomarkers (NPs and hs-cTn) for the early identification of the presence of myocardial dysfunction and/or injury and to significantly reduce the duration and costs of hospitalization [8,10,[14][15][16][17][18][19][20]56,76,77,98,100,101]. Moreover, specific cardiac biomarkers (especially hs-cTnI and hs-cTnT) are useful predictors of mortality and MACE in patients admitted to the ED with suspected acute cardiovascular disease [17,19,22,53,84,[102][103][104].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to balance the risk between a hasty discharge versus the potential harms caused by a cardiac assessment in patients admitted to the ED with suspected acute cardiovascular disease, the recent expert documents and guidelines recommend the measurement of specific cardiac biomarkers (NPs and hs-cTn) for the early identification of the presence of myocardial dysfunction and/or injury and to significantly reduce the duration and costs of hospitalization [8,10,[14][15][16][17][18][19][20]56,76,77,98,100,101]. Moreover, specific cardiac biomarkers (especially hs-cTnI and hs-cTnT) are useful predictors of mortality and MACE in patients admitted to the ED with suspected acute cardiovascular disease [17,19,22,53,84,[102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…In patients admitted to the ED with suspected ACS, including those with AHF, the measurement of hs-cTnI and hs-cTnT should be considered the first-line biomarkers, in order to identify the presence of myocardial injury and to quickly rule out ACS, leading to a significant reduction in the duration and costs of hospitalization [14][15][16][17][18][19][20]56,76,77,88,[100][101][102]. Furthermore, several recent clinical studied have demonstrated that hs-cTnI and hs-cTnT are useful predictor biomarkers for mortality and MACE, even in the setting of AHF [17,19,22,53,84,[102][103][104]. In particular, according to the Fourth Universal Definition of Myocardial Infarction [8], an increase in hs-cTnI and hs-cTnT above the 99th percentile URL value proves the presence of myocardial injury in AHF patients.…”
Section: Role and Advantages Of Poct Methods For Cardiac Troponin In ...mentioning
confidence: 99%
See 2 more Smart Citations